THE ROLE OF METACOGNITIVE REFLECTION AS A PSYCHOLOGICAL FACTOR IN STUDENTS’ ACADEMIC SUCCESS (International Conference on Education, Psychology and Humanities, 2026)
Metacognitive reflection is a psychological factor that strongly influences students’ academic success because it helps them monitor, evaluate, and regulate their own learning processes. Through reflection, students become more accurate in judging their study strategies, more capable of adjusting behavior, and more likely to adopt effective learning habits. Recent evidence shows that reflective opportunities can improve confidence, preparedness, retention, and semester GPA, especially when metacognition is taught explicitly and supported through structured interventions. This article presents an IMRAD-style synthesis of ten verifiable sources and explains how metacognitive reflection contributes to academic success through motivation, self-regulation, and strategic learning.
Keywords: metacognitive reflection, metacognition, self-regulated learning, academic achievement, reflective learning, higher education, cognitive regulation, learning strategies, reflective practice, student learning.